Chemical characterization and study of the genotoxicity and induction of oxidative stress of particulate material pm10 from the urban area of cuenca ecuador [Caracterización química del material particulado PM10 de la zona urbana de Cuenca- Ecuador e investigación de su genotoxicidad e inducción de estrés oxidativo en células epiteliales alveolares A549] - Bailon Moscoso, N. (2014)
Exposure to environmental particles is a risk factor that causes damage to human health, such as respiratory and cardiovascular diseases and cancer. The toxicity and inflammatory effects of these particles is related to their size and chemical characteristics. The aim of this study was to determine the chemical characteristics of the aqueous fraction of Particulate Matter PM10, collected in three monitoring sites Cuenca-Ecuador, and to evaluate their genotoxic activity and induction of reactive oxygen species (ROS) in human alveolar epithelial cell line A-549. Samples were collected using a low volume equipment. Particulate matter concentrations determined by gravimetric analysis in the three study points exceeded the 50 ug / m3 limit stated in the Ecuadorian legislation. In the characterization of the aqueous solution the presence of anions (Cl-, NO3 -, SO4 -2) and heavy metals (Cr, Fe, Ni, Zn, Cu, Mn) was determined by ion chromatography techniques and atomic absorption spectroscopy, respectively; SO4 -2 and Fe showed the highest concentrations. The A-549 cells were exposed to different concentrations (0.82, 1.25 and 1.63 m3 / mL) fraction of water-soluble PM10, in order to observe the possible genotoxic effect by the comet assay and the amount inducing reactive oxygen species by fluorimetry. It was finally determined that the aqueous -soluble extracts of PM10 induce cell damage under (type I), and increase the production of ROS in cells A-549, which could pose a risk to the health of the exposed population of the city of Cuenca © 2015, Asociacion Espanola de Toxicologia. All rights reserved.